Proteinase Activated Receptors Mediate the Trypsin-Induced Ca2 + Signaling in Human Uterine Epithelial Cells - Shmygol, Anatoliy; Brosens, Jan J. (Frontiers in Cell and Developmental Biology, 2021)
Embryo implantation is a complex and tightly regulated process. In humans, uterine luminal epithelium functions as a biosensor gauging the embryo quality and transmitting this information to the underlying endometrial stromal cells. This quality control ensures that only high-quality embryos are implanted, while aberrant ones are rejected. The mechanisms of the embryo-uterine lining crosstalk remain incompletely understood. A serine protease trypsin secreted by the blastocyst has been implicated in the cross-signaling. Here we address the mechanisms by which trypsin triggers the intracellular calcium signaling in the uterine epithelium. We found that protease-activated G-protein coupled receptors are the main mechanism mediating the effects of trypsin in human uterine epithelium. In addition, trypsin activates the epithelial sodium channels thus increasing the intracellular Na+ concentration and promoting Ca2+ entry on the reverse mode of the sodium/calcium exchanger.